Alteration in elemental and functional composition of heated peat humic acids; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Chukhareva N. V. Natalia Vyacheslavovna (2016, 2016)
Title screen